Use of ablation and ultrasonic aspiration at primary debulking surgery in advanced stage ovarian, fallopian tube, and primary peritoneal cancer. Issue 7 (July 2020) - Li, Sue; Manning‐Geist, Beryl; Gockley, Allison; Ramos, Amanda; Sisodia, Rachel C.; Del Carmen, Marcela; Growdon, Whitfield B; Horowitz, Neil; Berkowitz, Ross; Worley, Michael
ABSTRACT : Objectives : Ovarian cancer patients with miliary disease have the lowest rates of complete surgical resection and poorest survival. Adjunct surgical techniques may potentially increase rates of complete surgical resection. No studies have evaluated the use of these techniques in primary debulking surgery for ovarian cancer patients with miliary disease. The aim of this study was to examine the use of adjunct surgical techniques during primary debulking surgery for patients with advanced epithelial ovarian, fallopian tube, and primary peritoneal cancer with miliary disease. Methods : Medical records of patients with International Federation of Gynecology and Obstetrics (FIGO) stages IIIC‐IVB epithelial ovarian, fallopian tube, or primary peritoneal cancer with miliary disease undergoing primary debulking surgery from January 2010 to December 2014 were reviewed. Adjunct surgical techniques were defined as ultrasonic surgical aspiration, argon enhanced electrocautery, thermal plasma energy, and traditional electrocautery ablation. Patients undergoing surgery with and without these devices were compared with respect to demographics, operative characteristics, postoperative complications, residual disease, progression free survival and overall survival. Results : A total of 135 patients with miliary disease underwent primary debulking surgery, of which 30 (22.2%) patients used adjunct surgical techniques. The most common devices were ultrasonic surgical aspiration (40%) and argon enhanced electrocautery (36.7%). The most common sites of use were diaphragm (63.3%), pelvic peritoneum (30%), bowel mesentery (20%), and large bowel serosa (20%). There were no differences in age, stage, primary site, histology, operative time, surgical complexity, or postoperative complications for patients operated on with or without these devices. Volume of residual disease was similar (0.1‐1 cm: 60% with adjunct techniques versus 68.6% without; complete surgical resection: 16.7% with adjunct techniques versus 13.3% without; p=0.67). For patients with ≤1 cm residual disease, median progression free survival (15 versus 15 months, p=0.65) and median overall survival (40 versus 55 months, p=0.38) were also similar. Conclusion : Adjunct surgical techniques may be incorporated during primary debulking surgery for patients with advanced epithelial ovarian, fallopian tube, or primary peritoneal cancer with miliary disease; however, these do not improve the rate of optimal cytoreduction.